Mapping the Nordic mining and metal industry : for the purpose of enhancing and developing its innovative capability - Kurkkio, Monika; Frishammar, Johan; Söderholm, Patrik; Ejdemo, Thomas (Luleå tekniska universitet, Industriell Ekonomi, 2014)
First, a descriptive overview of the Nordic mining and metal industry is provided. It shows that thereare a number of disparities among the firms in theNordic mining and metal industry, but there are alsomany similarities. Finland and Sweden both havewell-developed mining and metal industries. The geo-logical conditions are comparable and, consequently,production and outlook are in the main relativelysimilar for firms producing minerals and metals.Norway’s mineral and metal production mostlyconsists of industrial minerals, the potential of whichis promising. Greenland has great potential in its newmineral deposits. However, there are several challenges(e.g. difficulties in accessing the new mineral deposits,and problems related to infrastructure and a shortageof skilled workers) which need to be overcomebefore the mineral deposits can be explored.Key challenges for innovation have been identifiedand categorised into (a) specific challenges for keyactors and (b) cross-border challenges involvingseveral groups of producing firms in the Nordicmining and metal industry. The major innovationchallenges specific to the mining companies arein-creased production costs,atraditional and conservativemind-setanda short-term focus on exploration.Majorinnovation challenges for the metal producers areprimarilyold production plants and technology, low profitmargins and lack of employees with the right type of skills.The equipment suppliers’ foremost challenges arethe difficulties ofconducting experiments and testsandgaining access to the right type of knowledge.The analysisshows thatdemand for sustainable mining, difficultiesrelated to the exploration of new mineral deposits, a conserv-ative attitude towards innovation in the mining industry,global competition and procurement methods that emphasisepure cost concerns and the absence of pilot and demonstra-tion plantsare at this time the foremost cross-borderchallenges for innovation within the Nordic miningand metal industry. The Nordic countries have large mineral and metal ...